2020
DOI: 10.22230/ijepl.2020v16n6a945
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge Mobilization for Impact: A Multi-Case Study of Education Organizations

Abstract: Using a multi-case design, this study draws on empirical evidence and literature to analyze the knowledge mobilization approaches in educational organizations. The sample consists of four different types of education organizations in Ontario, Canada: a school board, a university, a not-for-profit, and a professional association. Data sources include publicly available websites and documents (n = 63) and key informant interviews (n = 18). Although research impact was operationalized and observed differently in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 25 publications
1
12
0
Order By: Relevance
“…, 2017; Whitty & Wisby, 2017). In these kinds of policy developments, the issues of close‐to‐practice are bound up with the idea of research/practice partnerships (Malik, 2016). For example, in Ontario, the Knowledge Network for Applied Education Research (KNAER)1 was established through a tripartite agreement among the University of Toronto, Western University and the Ontario Ministry of Education.…”
Section: Education Research and Practicementioning
confidence: 99%
See 1 more Smart Citation
“…, 2017; Whitty & Wisby, 2017). In these kinds of policy developments, the issues of close‐to‐practice are bound up with the idea of research/practice partnerships (Malik, 2016). For example, in Ontario, the Knowledge Network for Applied Education Research (KNAER)1 was established through a tripartite agreement among the University of Toronto, Western University and the Ontario Ministry of Education.…”
Section: Education Research and Practicementioning
confidence: 99%
“…The aim of KNAER was to advance and apply robust evidence of effective practices through facilitating networks of educators and researchers to work collaboratively, to apply research to practice. Likewise, the Ontario Education Research Panel was established to facilitate discussion and collaboration among Ontario’s school boards, faculties of education and researchers, relating to opportunities for, and impediments to, the advancement of research and the potential for future partnerships (Malik, 2016). Similar in notion are the research–practice partnerships in the USA.…”
Section: Education Research and Practicementioning
confidence: 99%
“…Limited application of research in practice has been reported in previous studies (Malik, 2020). Several case studies in evidence-based disciplines such as health sciences and education highlight KMb's positive contribution towards fillling the gap between research and practice, while they also acknowledge difficulties arise in KMb implementation (La Velle & Flores, 2018;Cooper, Klinger, & McAdie, 2017).…”
mentioning
confidence: 98%
“…application and transfer scientific results beyond academia, to help practitioners, policy makers, and even the public make knowledge-informed professional and public decisions (Malik, 2020). This phenomenon is a set of complex, interlocking processes facilitating "the reciprocal and complementary flow and uptake of research knowledge" (SSHRC, 2019), involving different actors from and beyond academia.…”
mentioning
confidence: 99%
See 1 more Smart Citation